Some aspects of the population ecology of Chinese soft-shelled turtle (Pelodiscus sinensis) in Pampanga, Luzon, Philippines - Apostol, Nikka P.; Bacunot, Lowie S.; Mascareñas, Ma. Anthea Z. (2014., 2014)
The Chinese soft-shelled turtle (Pelodiscus sinensis) recently gained popularity because of claims of its infestations in different aquaculture areas in the Philippines, specifically, in San Luis, Pampanga. Efforts at managing populations of this turtle were implemented by the government and other local agencies without any attempt to understand the ecology of the species. For this reason, this study aims to provide a more accurate estimate of the P. sinensis population using the Multiple Capture Mark Recapture and Removal Sampling methods. Sex ratio and population age pyramid were used to indicate potential trends in population changes and gut content analyses were also conducted to verify the claim that the turtles feed on aquacultured fish. Population estimates using the Schnabel index was 5259±2234. The study foresees a possible increase in the P. sinensis population derived from the higher female to male sex ratio of juveniles of 1.68 : 1 and also the pyramidal structure of the age distribution; however, the sex ratio of adult turtles (1.02 Female : 1 Male) did not support this hypothesis. As for the claim of the locals that P. sinensis is a pest, the gut contents analysis was able to provide clear evidence that the turtle does prey on tilapia (Oreochromis niloticus) and other molluscs. However, aquaculture destruction in Pampanga could not be solely attributed to P. sinesis since there are other predator populations in the area. Although this study confirmed that P. sinensis feeds on local fishes, longer term monitoring is still needed to verify its reputation as a pest -- Author's abstract.
Thesis (Bachelor of Science in Biology) -- University of the Philippines Baguio, 2014.
Includes bibliographical references (leaves 36-39).
Keywords: Soft-shelled turtles -- Ecology -- Philippines -- Pampanga